Secondo : a platform for moving objects database research - Tan, Andrew Wee Teck (2014)
The purpose of this report is to explain and demonstrate a prototype for managing moving objects in Database Management Systems (DBMS). SECONDO is developed over the last decade by University of Hagen in Germany. It is an “extensible open-source DBMS environment” with “no fixed data model”. This framework forms a new generic environment that is more flexible than common extensible and object-relational DBMS. Hence, it is suitable for research prototyping and teaching in any particular context on moving objects databases.